2015
DOI: 10.1161/circheartfailure.115.002414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Stratification for Primary Prevention Implantable Cardioverter Defibrillators

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 36 publications
4
57
0
2
Order By: Relevance
“…Nevertheless, therapy rates in our cohort are comparable to those reported in recent observational studies in Canada, Europe, and the United States 30, 31, 32, 33. In the OMNI (Assessing Therapies in Medtronic Pacemaker, Defibrillator, and Cardiac Resynchronization Therapy Devices) study, for example, 25% received an appropriate therapy over a mean of 39 months compared with 20% over 27 months in the LS‐ICD 33.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, therapy rates in our cohort are comparable to those reported in recent observational studies in Canada, Europe, and the United States 30, 31, 32, 33. In the OMNI (Assessing Therapies in Medtronic Pacemaker, Defibrillator, and Cardiac Resynchronization Therapy Devices) study, for example, 25% received an appropriate therapy over a mean of 39 months compared with 20% over 27 months in the LS‐ICD 33.…”
Section: Discussionsupporting
confidence: 83%
“…The negative impact on mortality of ventricular tachycardia or ventricular fibrillation needing shocks has been consistently seen in different primary prevention clinical trials . Studies to define predictors of shocks and mortality have been done in primary prevention patients with aims to shift clinicians’ focus toward mitigating such risks . Although it has been consistently demonstrated that secondary prevention patients have higher incidence of shocks, there is not a large amount of comparative data with primary prevention patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Programming strategies for primary prevention patients were not standardized in the implanting centers, but previous reports of our group have shown that the shocks and ATP incidence rates were similar to the contemporary studies with delayed detection therapy groups, so an impact on mortality risk based on this is very unlikely. The score used to control for baseline differences was designed and validated on a sample derived from a primary prevention cohort and was extended to the secondary prevention sample in the analysis . Our analysis was focused on assessing outcome after a single ICD shock or ATP and did not evaluate multiple shocks or ATPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Using multivariable regression statistics of the primary endpoint, we will be able to calculate an adequately powered hazard ratio of the ICD survival effect (as the primary measure of ICD benefit) in the overall cohort and predefined subgroups. 50,57,59,60 Cost-effectiveness in the overall trial population and in subgroups and the variation in EU countries can be analysed. Concerning these outcomes, the results will be able to confirm known independent risk factors and possibly detect new ones.…”
Section: Discussionmentioning
confidence: 99%